2004
DOI: 10.1080/20702620.2004.10431761
|View full text |Cite
|
Sign up to set email alerts
|

Stand biomass and volume estimation for Miombo woodlands at Kitulangalo, Morogoro, Tanzania

Abstract: SYNOPSISTree volume and biomass equations developed for Kitulangalo area in Morogoro, Tanzania ignored small branches and small trees. Consequently, this study was carried out to develop new individual tree volume and biomass equations, and assess current regeneration status, biodiversity and yield ofmiombo woodlands of the area. Volume and biomass equations based on stump diameter for the estimation of volume and biomass of felled trees were also developed. A total of 30 trees were measured for stump diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 3 publications
7
52
5
Order By: Relevance
“…Our findings that height and/or crown area does not substantially improve the predictive power of diameter models contradict recent findings in Peru, which show that crown radius greatly improves model performance, especially for the largest trees [35]. The majority of allometric models in the miombo ecoregion use DBH as the sole predictor variable, e.g., Chamshama et al [22], Ryan et al [21] Chidumayo et al [8] and Mugasha et al [23]. There are few models that include height as a second variable to DBH, e.g., Chamshama et al [22].…”
Section: Performance Of New Allometric Modelscontrasting
confidence: 90%
See 3 more Smart Citations
“…Our findings that height and/or crown area does not substantially improve the predictive power of diameter models contradict recent findings in Peru, which show that crown radius greatly improves model performance, especially for the largest trees [35]. The majority of allometric models in the miombo ecoregion use DBH as the sole predictor variable, e.g., Chamshama et al [22], Ryan et al [21] Chidumayo et al [8] and Mugasha et al [23]. There are few models that include height as a second variable to DBH, e.g., Chamshama et al [22].…”
Section: Performance Of New Allometric Modelscontrasting
confidence: 90%
“…The accuracy of the models varied across the evaluated sites and trees of different diameter classes (Figure 3). In the absence of local or country-specific allometric models, mixed species models by Chamshama et al [22] and Ryan et al [21] appear as the most appropriate for estimating aboveground biomass in Kasungu and Neno, which were both dominated by small diameter trees. Breaking down the error into DBH size classes showed that all published models overestimated biomass with a greater bias in trees with a DBH greater than 30 cm.…”
Section: Performance Of Published Allometric Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a figure of database and magazine that in attendance nonpayment weakening equations, stratified by rainfall government and section [16,19,20]. These failures to pay equations, based on a huge sample of vegetation, are frequently practical as the age group of confined allometric equations is over and over again not reasonable.…”
Section: Carbon Sequestration Potential Of Forestsmentioning
confidence: 99%